2013
DOI: 10.1111/tme.12043
|View full text |Cite
|
Sign up to set email alerts
|

Significance of screening antibodies to hepatitis B virus core antigen among Syrian blood donors

Abstract: Our results suggest including anti-HBc as an additional screening test for blood donors in Syria to reduce the risk of HBV transmission. As the most cost-effective measure, anti-HBc-positive donors should be tested quantitatively for anti-HBs and only donors with no or low (<100 IU L(-1) ) anti-HBs should be deferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
3
7
1
Order By: Relevance
“…Evidently, hepatitis seroprevalence among multitransfused patients is reflected by the seroprevalence among healthy blood donors 12. This is underlined by the consistency of our findings among multitransfused patients (HBsAg, 0.62%; anti-HBc, 12.5%) with a previous report on HBV seroprevalence among Syrian blood donors (HBsAg, 1.3%; anti-HBc, 11.2%,7 which coincides with other countries such as Jordan,2 Iran1,13 and Pakistan 14…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Evidently, hepatitis seroprevalence among multitransfused patients is reflected by the seroprevalence among healthy blood donors 12. This is underlined by the consistency of our findings among multitransfused patients (HBsAg, 0.62%; anti-HBc, 12.5%) with a previous report on HBV seroprevalence among Syrian blood donors (HBsAg, 1.3%; anti-HBc, 11.2%,7 which coincides with other countries such as Jordan,2 Iran1,13 and Pakistan 14…”
Section: Discussionsupporting
confidence: 88%
“…Viral nucleic acids were extracted using MagNA Pure Compact Nucleic Acid Isolation kit (Roche Diagnostics, Mannheim, Germany) according to the manufacturer’s instructions. HBV DNA and HCV RNA were detected by real-time PCR using LC-FastStart DNA Master HybProbe and LC-RNA Master HybProbe kits, respectively, on the LightCycler instrument (Roche Diagnostics, Mannheim, Germany) as previously described 7,9…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of hepatitis B is 1.7% and the prevalence of hepatitis C is 0.4% in Syrian refugees. While these results are very similar to the results of the studies on blood donors in Syria, they are found to be lower than the 4.2% HBsAg seropositivity and 1.0% anti-HCV seropositivity values determined by [25,26] Koruk et al in their study in the city center of Şanlıurfa in 2008 [14]. The rate of Anti-HBs positivity is 9.4% in blood donors in Syria and 25.2% in Syrian refugees.…”
Section: Discussionsupporting
confidence: 84%
“…In Muselmani et al study done in AL Assad university hospital on the blood donors (2013), they found the prevalence of HBV to be 1.3 % [25], which is lower than in our study, probably this is because of the war that happened in that country since 2013 with near complete collapse of the health system. Beside this since beginning of the war in Syria hundreds of mass casualties had happened in the country with a large numbers of injuries, operations and blood transfusions.…”
Section: Discussioncontrasting
confidence: 79%